Estudo do potencial de regeneração natural: uma análise da chuva de sementes e do estrato regenerante da vegetação ciliar na bacia hidrográfica do rio Taperoá, semiárido paraibano, Brasil - Barbosa, Francisca Maria (2008)
It was aimed at to study the natural regeneration in a ciliary area of Caatinga in the basin of the river Taperoá, semi-arid paraibano. The research was accomplished in the january/2004 period the december/2006 and it embraced the riverine area of the stream of Cazuzinha (7º26 13 S and 36º54 30 W; altitude 564-579 m). In that sense, the work understood the following stages: 1) characterization of the composition and of the contribution of the rain of seeds; 2) evaluation of the density, germination and flora of the bank of seeds of the soil in two differentiated stations and 3) analysis of the composition, structures and dynamics of the natural regeneration. In the first stage they were established 102 contiguous parcels of 10 X 10 m (1,02 ha). The collections were accomplished monthly. The collected material was conditioned in paper bags, which were identified with the number of the collector and the portion in the which was located. In the rain of seeds, 6.975 seeds belonging to 80 species were registered. The found density was of 775 seeds/m2/year. It was still verified for the community a pattern of having accentuated seasonality in the seeds production. The herbaceous having been the group that produced most of the sample seeds and the largest wealth of species. Like this, the seeds anemochorics were predominantly dispersed in the dry period. Most of the species zoochorics liberated your fruits in the rainy period, in other words, at that time of better conditions of ripening of the fruit, dispersion and seedling establishment. For the species autochorics the pick of dispersed seeds happened in the dry period. Related to the ecological groups the initial secondary species contributed with the percentile largest of species and liberated seeds. The index of diversity of Shannon was relatively inferior when compared with found for the bank of seeds of the soil. Particularly related to the bank of seeds, it is had that were collected in the 36 raffled parcels, for period amostral (dry and rainy), in each one of these, a sample of soil of 0,25 m2 to the depth of 5 cm. The florístic the identification of the species was based mainly on the morphology of the seedling. The density of the bank was evaluated by the method of seedling emergency. The composition floristc of the bank was represented by 165 species, being the end of the dry and rainy periods represented respectively by 122 and 124 species. The herbaceous ones composed 97% of the seeds germinated in the bank, being 95% in the end of the dry period and 99% in the end of the rainy station. The density of germinated viable seeds was larger in the end of the dry period (877 seeds/m2) than in the end of the rainy station (616 seeds/m2). Like this, it was verified that the end of the rainy period presented the largest wealth of species, however, in the end of the dry period it happened the largest seedling density for area. Does the analysis of the composition, structure and was dynamics of the natural regeneration verified with the distribution of 72 xviii parcels of 1 X 1 m along the course of water, enrolling the woody saplings with height ≥ 0,20 m and DNS < 3 cm. Rose 36 species and 380 individuals in the first inventory and 39 species and 391 individuals in the second. Most of the species belongs to the pioneers' ecological group and secondary initials, being the autochory and animal dispersal the predominant dispersal syndromes. Only three species happened in all the size classes in the two inventories and the largest indexes of natural regeneration were obtained by Croton rhamnifolioides, Combretum pisonioides, an indeterminate specie, Manihot glaziovii and Ziziphus joazeiro. The rates of ingrowths and mortality for the community were 13,8% and 11,3% respectively. The diversity values and equability in evaluations were 2,888 nats.ind.-1 and 0,806 and 2,879 nats.ind.-1 and 0,786 respectively. In general, the data demonstrate that in the ciliary areas of the semi-arid the saplings bank is of largest importance for the regeneration of those atmospheres, because it allows the establishment of pioneering species and secondary initials providing an increment in the wealth of woody species in the community.